Peran Penerapan ESG terhadap Kinerja Keuangan Perbankan pada Negara Terdampak Tekanan Ekonomi Global - Dian Fajarini; Emi Maimunah; Irma Febriana (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the effect of the implementation of ESG (Environmental, Social, and Governance), global economic pressures reflected through inflation and exchange rates, as well as bank size on banking performance proxied by Return on Assets (ROA). In addition, this study also aims to examine whether the implementation of ESG is capable of mitigating the impact of global economic pressures on banking performance in countries affected by global economic pressures. The research period covers 2015–2024, with the banking sectors in Indonesia, Brazil, South Africa, the Philippines, and India as the research objects. The results indicate that the ESG variable has a negative and significant effect on banking performance. The exchange rate variable is found to have a positive and significant effect on banking performance. Meanwhile, the inflation and bank size variables do not show any effect on banking performance. Furthermore, the findings also reveal that the ESG–exchange rate moderation variable has a positive and significant effect on banking performance. These findings indicate that the implementation of ESG is able to mitigate the impact of global economic pressures originating from exchange rate fluctuations on banking performance in the five countries affected by global economic pressures.